Testing hearing the making of modern aurality - Tkaczyk, Viktoria 1976-; Mills, Mara ca. 20./21. Jh; Hui, Alexandra 1980- (Oxford scholarship online, 2020)
'Testing Hearing' argues that the modern cultural practices of hearing and testing have emerged from a long interrelationship